2019
DOI: 10.1177/0898264319848866
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Health Outcomes Associated With Hearing Loss and Hearing Aid Use Among Older Adults

Abstract: Background: This study recruited older adults to explore physical and psychosocial conditions and other health outcomes associated with hearing loss (HL) and hearing aid use. Method: Survey data were used to categorize 20,244 participants into five groups: no HL, unaided mild HL, aided mild HL, unaided severe HL, and aided severe HL. Results: Individuals with unaided severe HL were more likely to report poor-fair self-rated health and were less likely to leave the home, or exercise 4 to 7 days per week, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 63 publications
4
58
0
Order By: Relevance
“…Included studies were published between 1982 and 2019. Of the included studies, 7 were in the United States, 23,24,30,32-35 4 in the Netherlands, 25-28 2 in Canada, 29,36 and 1 in Japan. 31 Most studies (12/14) were cross-sectional, and 2 were longitudinal in design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies were published between 1982 and 2019. Of the included studies, 7 were in the United States, 23,24,30,32-35 4 in the Netherlands, 25-28 2 in Canada, 29,36 and 1 in Japan. 31 Most studies (12/14) were cross-sectional, and 2 were longitudinal in design.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included both men and women, but 1 study included men only 32 and 2 studies reported results separately for men and women. 29,35…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations